(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
The discovery of high-temperature superconductivity in the system Tl-Ba-Ca-Cu-O initiated active research structure and properties of this class of superconductors. Determined that the system consists of two phases homologous Tl and Tl2 with basic stoichiometric formulas TlBa2Can-1CunO2n+3 and Tl2,2Ba2Can-1CunO2n+4 (n = 1-5). These phases are integrated structure consisting of active layers of superconducting Can-1(CuO2)n and inactive layers BaO. A total of Tl-Ba-Ca-Cu-O superconductors were obtained from the temperature of transition to the superconducting state 80-135 C. However, in structural terms, remain open questions about the nature of defects in structures thallium phases: the availability of vacancies, isomorphic substitution, displacement of atoms in the cation or anion sublattice and others. The electrical properties of ceramics of the same stoichiometric quite sensitive to the conditions of preparation and may vary from characteristic of a superconductor with Tc = 135 K to dielectric characteristic. Synthesized compounds of Tl2-xBixSr2Can-1CunOy (n = 2, 3, 0 ≤ x ≤ 0,5) by solid phase synthesis. An X-ray analysis and measurement of the electrical properties of samples with different composition. Determined homogeneity and investigated changing the parameters of the unit cell. The size and shape of particles comprising the ceramics were studied using scanning electron microscopy. Physical properties of superconductors with the addition of bismuth worse, transition temperature to the superconducting state decreases.